An updated review of Rubus ellipticus (an edible shrub), its bioactive constituents and functional properties (Sciences of Phytochemistry, 2022)
The vast majority of people continue to view medicinal plants as a low-cost source of medications and treatments. Numerous trees, herbs, plants, and shrubs have been used as remedies for various ailments since the dawn of time. Rubus ellipticus Smith, a weedy wild raspberry that flourishes in damp woods at high elevations, particularly those in the Himalayas and the Nilgiris area, is one of the important ethnomedicinal plants in the genus Rubus. Traditional Tibetan medicine places a great deal of importance on the plant R. ellipticus. Because of the abundance and diversity of phenolics and flavonoids in fruits or berries, which have a high concentration of both, they are generally regarded as inherently healthful foods. The roots and leaves, as well as the fruit, have traditionally been used as therapeutic agents for several illnesses including colic pain, gastrointestinal discomfort, wound healing, diarrhea, antifertility, antibacterial, analgesic, epilepsy, and others. The objective of the current review is to concentrate on the pharmacological characteristics, nutrition profile, phytoconstituents, and folkloric therapeutic applications of R. ellipticus, therefore achieving the review's overall subject.